P100: MicroRNA-21, -155, -200c and -205 in carcinogenesis of larynx. Issue 1 (November 2015) - Nikitina, E.; Cheremisina, O.; Kulbakin, D.; Litviakov, N.
Abstract : The purpose of the study was to access pattern of microRNA expression in tissue of precancerous lesions and larynx cancer. A total of 25 people with a diagnosis of dysplasia II–III ( n  = 10), control group (dysplasia 0, n  = 15) and larynx cancer patients ( n  = 46) were examined. Fresh frozen biopsies and adjacent normal epithelium were used. The diagnosis was verified by histology. All qRT-PCR data were analyzed using the Pfaffl analysis. Multiplex RT-PCR on miRNA templates were performed as described by Chen et al. (2005). TaqMan miRNA assays (Iyevleva et al., 2012) were used to quantify expression of mature miRNAs of interest (miR-18a, -21, -155, -200a, -200c, -205, -221, -494). Data were analyzed using Welsh t-test with a 5% FDR correction. According to our results, aberrant expression of some miRNAs was showed. There was no significant differences in miRNA expression in a total group ( n  = 25) although a trend towards overexpression of oncogenic miRNA-21 and -155 according to severity of dysplastic changes in a tissue were present. Detailed analysis showed significant overexpression of that miRNAs as well as miRNA-200c and -205 in a group of dysplasia II- III against control group (15 vs 10, p  = 0.019, p  = 0.045 and p  = 0.020, p  = 0.038, respectively) but these results did not meet 5% FDR correction. Data showed overexpression of the same microRNA (-205, -155, -200 and -21) in larynx cancer patients compared to control group (46 vs 15, p  = 0.0002, p  = 0.008, p  = 0.009, p  = 0.013, respectively). It should be pointed that microRNA pattern both in larynx cancer and patients with dysplasia II-III was very close showing similarity of these groups at molecular level. Frequency of cases with microRNA-205 overexpression was 2.98 times higher in cancer patients than in those who had no malignant transformation (CI 95%, 1.41–16.26, p  = 0.007). Data showed that up regulation of microRNA-205 could be a marker of disease progression (OR = 4.79). Three other microRNAs did not show any promising results as biomarkers of cancer progression but data obtained has interesting fundamental value. These miRs (-21, -155, -205 and -200c) are known to be regulators of processes that play an emergent role in carcinogenesis and our results obtained in vivo highlight and expand knowledge about some aspects of larynx cell transformation. Data suggest that miRNAs changing its expression according to dysplasia progress and could be important players in complex process of carcinogenesis as well as could be potential markers of disease progression.